2010
DOI: 10.1007/s12149-010-0409-3
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-123-metaiodobenzylguanidine imaging can predict future cardiac events in heart failure patients with preserved ejection fraction

Abstract: (123)I-MIBG imaging provides independent prognostic information in patients with HFPEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 32 publications
(44 reference statements)
3
29
0
1
Order By: Relevance
“…A diabetic heart is also likely to have impaired 123 I-MIBG activity (low HMR and 123 I-MIBG defect) in association with disease progression (14). Table 1 summarizes major investigations that prospectively monitored patients with chronic HF for more than 2 y with an endpoint of cardiac death (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). (26).…”
Section: Clinical Use Of 123 I-mibg Studies Leading To Japanese Nuclementioning
confidence: 99%
“…A diabetic heart is also likely to have impaired 123 I-MIBG activity (low HMR and 123 I-MIBG defect) in association with disease progression (14). Table 1 summarizes major investigations that prospectively monitored patients with chronic HF for more than 2 y with an endpoint of cardiac death (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). (26).…”
Section: Clinical Use Of 123 I-mibg Studies Leading To Japanese Nuclementioning
confidence: 99%
“…Furthermore, patients with the lowest uptake, as reflected by the heart-to-mediastinal ratio, or with the fastest washout from the heart tend have the poorest prognosis (8,9). Multiple studies suggest that 123 I-MIBG can be used as an independent predictor of HF progression and cardiac mortality (11)(12)(13).…”
Section: Hear T Failure (Hf) Is a Growing Health Problem In The Unitedmentioning
confidence: 99%
“…As outlined above, although previous studies have already reported similar relationships with 123 I-mIBG planar scintigraphic indices in HFpEF patients (18,19), the novelty of this study relates to use of 11 C-HED PET imaging, which allows for improved global and regional quantification of SNS innervation due to better spatiotemporal resolution and more quantitative image analysis than conventional 123 I-mIBG planar imaging. In this study, 11 C-HED-derived indices of cardiac sympathetic function were related to transthoracic echocardiographic indices of diastolic dysfunction as established in the 2009 recommendations of the American Society of Echocardiography (ASE) and European Association of Echocardiography (EAE) (21).…”
mentioning
confidence: 75%
“…Along these lines, decreased global 11 C-HED RI is independently predictive of worse cardiovascular prognosis and all-cause mortality in patients with HFrEF (23,24). More relevant to the topic at hand, other studies have reported that the 123 I-mIBG heart-to-mediastinal ratio and washout rate can discriminate between HF severity and can predict worse prognosis and future cardiac events in HFpEF patients (18,19).…”
mentioning
confidence: 96%
See 1 more Smart Citation